Anisotropic distribution of dislocations density in tensile strained GaP/GaAs epilayers. (August 2018) - Kumar, Ravi; Dixit, V.K.; Sharma, T.K.
Abstract: An anisotropic distribution of dislocations density is observed by performing high resolution X-ray diffraction measurements on tensile strained GaP/GaAs epilayers. The anisotropy is evident from a large variation in the width of rocking curves for (400) reflections along [ 01 1 ¯ ] and 0 1 ¯ 1 ¯ directions. In a recent article [J. Appl. Phys. 120, 135307 (2016)], we have shown that 90° partial dislocations (α dislocations) are responsible for initial relaxation along [ 01 1 ¯ ] direction after which 60° perfect dislocations (β dislocations) dominates the relaxation process. In this article, a method based on the random distribution of dislocations is proposed for estimating the density of dislocations in tensile strained zinc blende epitaxial layers. The proposed method is helpful in estimating the density of 90° partial and 60° perfect dislocations in GaP/GaAs epilayers. It is found that the density of dislocations is generally underestimated by the earlier reported methods. Highlights: HRXRD is a very effective tool in estimating the asymmetry of dislocation density. It is used to study tensile strained GaP/GaAs epilayers. A new method estimates the density of 90° partial and 60° perfect dislocations. FHWM is replaced by tilt along with the respective component of Burgers vector. It is found that the dislocation density is underestimated by earlier methods. Density of 90° partial dislocations, can also be measured.